The Role of the Regional Indonesian Broadcasting Commission in Improving the Quality of Local Religious Broadcasts - Khadafi, Muammar (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2023)
This research examines the participation and activities carried out by the Yogyakarta Province Regional Indonesian Broadcasting Commission (KPID) to improve the quality of broadcasting of religious shows as local broadcasts. KPID Yogyakarta Province is a supervisory body and takes action if broadcasting institutions do not comply with broadcasting regulations. As a state regulatory body with authority at the local level to improve broadcast quality, KPID Yogyakarta Province can take action if violations are found regarding broadcasts presented by broadcasting institutions. Using a qualitative approach with the application of descriptive analysis techniques, this research uses the theory of role aspects according to Biddle and Thomas in the form of Expectation, Norm, Performance, Evaluation, and Sanction. The results of this research produced several findings. First, in the expectation aspect, KPID Yogyakarta Province hopes that religious shows can become events that are popular and needed by the public. Second, regarding the Norm aspect, KPID Yogyakarta Province uses the 2002 Broadcasting Law No. 32, Broadcasting Behavior Guidelines / Broadcast Program Standards (P3/SPS), and 2016 Regional Regulation No. 13 concerning Broadcasting Operations as a valid guideline for improving the quality of local broadcasts on religious broadcasts. Third, in terms of performance, KPID Yogyakarta is involved in intense activities with local television stations, the government, and the community. Fourth, in the Evaluation and Sanction aspect, Yogyakarta Province KPID follows up on indications of violations and gives several award categories in the form of the best Religion and Belief Broadcasts every year to broadcasting institutions that have complied with broadcasting regulations.